Fentanyl in North America: Current Trends and Strategies - Victoria Dittmar (The Journal of Intelligence, Conflict and Warfare)
On February 20th, 2025, Ms. Victoria Dittmar presented “Fentanyl in North America: Current Trends and Strategies” for February’s Digital Roundtable. The presentation was followed by a question-and-answer period with questions from the audience and CASIS Vancouver executives. The key points discussed were the current trends of synthetic drug markets, the effectiveness of steps being taken to dismantle the trade, and the ease of entering illicit markets.